Pesticide Container Rinsing - Thomas W. Dean; O. Norman Nesheim; Frederick M. Fishel (EDIS)
This document explains what procedures are involved in creating a legally empty container. This document is PI-3, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised May, 2005.